Increasing incidence and prevalence of multiple sclerosis in the Greater Hobart cohort of Tasmania, Australia. Issue 7 (16th May 2022) - Simpson-Yap, Steve; Atvars, Roberts; Blizzard, Leigh; van der Mei, Ingrid; Taylor, Bruce V
Abstract : Background: The Greater Hobart region (42.5°S) of Tasmania has consistently had the highest recorded prevalence and incidence rates of multiple sclerosis (MS) in Australia. We reassessed MS epidemiology in 2009–2019 and assessed longitudinal changes over 68 years. Methods: Cases recruited from clinic-based datasets and multiple other data sources. 2019 prevalence and 2009–2019 annual incidence and mortality rates estimated, and differences assessed using Poisson regression. Results: 436 MS cases resident on prevalence day were identified, and 130 had symptom onset within 2009–2019. Prevalence 197.1/100 000 (95% CI 179.4 to 216.5; 147.2/100 000 age standardised, 95% CI 126.5 to 171.3), a 36% increase since 2001 and 3.1-fold increase since 1961. 2009–2019 incidence rate=5.9/100 000 person-years, 95% CI 5.0 to 7.0 (6.1/1000 000 age standardised, 95% CI 4.7 to 7.9), a 2.8-fold increase since 1951–1961 and 65% since 2001–2009. 2009–2019 mortality rate=1.5/100 000 person-years, 95% CI 1.1 to 2.2 (0.9/100 000 age standardised, 95% CI 0.4 to 1.7), comparable to 2001–2009 (1.0/100 000) but reduced by 61% from 1951 to 1959 (2.1/100 000). 2001–2009 standardised mortality ratio=1.0 in 2009–2019, decreased from 2.0 in 1971–1979. Female:male prevalence sex ratio was 2.8, comparable to the 2009 value (2.6); incidence sex ratio (2.9) increased from 2001 to 9 (2.1). Comparisons with Newcastle, Australia (latitude=32.5°S) demonstrate a near complete abrogation of the latitudinal gradients for prevalence (ratio=1.0) and incidence (ratio=1.1), largely attributable to changing Hobart demography. Conclusions: Prevalence and incidence of MS continue to increase significantly in Hobart, alongside marked reductions in mortality and increased case longevity. The marked increase in incidence is of particular note and may reflect longstanding changes in MS risk behaviours including changing sun exposure, obesity rates, and smoking behaviours, particularly in females. Falling mortality contributes to increase longevity and prevalence, likely reflecting improved overall MS healthcare and implementation of disease-modifying therapy.